Peran Pembelajaran Teknologi Informasi dan Digitalisasi dalam Meningkatkan Kompetensi Siswa SMK: Tantangan dan Peluang di Era 4.0 - Mukharom Mukharom; Dita Rahmawati; Wahyudi Syaputra; Roberto Aldy Ratoeloedji (Lembaga Pengembangan Kinerja Dosen, 2025)
The Industrial Revolution 4.0 era requires vocational high school graduates to have strong digital competencies to face the challenges of an increasingly technology-based world of work. This study aims to analyze the role of Information Technology (IT) learning in improving the competency of vocational high school students, identify challenges in its implementation, and explore opportunities to strengthen IT learning. The study used a qualitative approach with subjects of students, teachers, and principals in two vocational high schools in Pagaralam City. Data were collected through interviews, observations, and documentation studies, and analyzed using qualitative descriptive techniques with data triangulation. The results of the study indicate that IT learning plays an important role in developing students' cognitive aspects (technological knowledge), technical skills (hard skills), and non-technical skills (soft skills). However, its implementation still faces various challenges, such as limited infrastructure, uneven teacher competency, gaps in technology access, and suboptimal curriculum development. On the other hand, there are great opportunities to strengthen IT learning through collaboration with industry, utilization of online learning resources, teacher training, and innovation in curriculum and learning methods. These findings are expected to be input for the development of more effective IT learning strategies in vocational high schools.